EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN TPS DENGAN PENDEKATAN SAVI TERHADAP PRESTASI DAN MOTIVASI BELAJAR DITINJAU DARI GAYA BELAJAR SISWA - Sutrisno, Sutrisno; Mardiyana, Mardiyana; Usodo, Budi (Jurnal Pembelajaran Matematika, 2013)
Abstract: The objective of this research is to determine the effect of the learning models on the learning achievement and motivation viewed from the learning styles of students. The learning models which were compared were the cooperative learning model of the STAD type with SAVI approach, the cooperative learning model of the TPS type with SAVI approach, and the conventional learning model. This research used the quasi experimental research method. Its population was all of the students in Grade VII of State Junior Secondary Schools in Batang regency in Academic Year 2012/2013. The samples of the research consisted of 300 students and were divided into three groups, namely: 100 students in control group, 102 students in experimental group 1, and 98 students in experimental group 2. The instruments of the research were questionnaire of learning style, questionnaire of learning motivation, and test of learning achievement. The data of the research were processed by using the multivariate analysis of variance with unbalanced cells. The results of the research are as follows: (1) both the cooperative learning model of the STAD type with SAVI approach and the cooperative learning model of the TPS type with SAVI approach, by and large, result in the best learning achievement, and the cooperative learning model of the STAD type with SAVI approach results in the best learning motivation; (2) in general, the best learning achievement is reached by the students with the auditory learning style, which is followed by those with the visual learning style and those with the kinesthetic learning style respectively, but on the learning motivation aspect there is not any best learning style of the three learning styles, and for sure it is known that the students with the auditory learning style has a better learning motivation than those with the kinesthetic learning style; (3) in the conventional learning model and in the cooperative learning of the STAD type, the learning achievement of the students with the visual learning style is the same as that of the students with the auditory learning style and that of the students with the kinesthetic learning style, but the learning achievement of the students with the auditory learning style is better than that of the students with the kinesthetic learning style; in the cooperative learning model of the TPS type with SAVI approach, the learning achievement of the students with the visual learning style is the same as that of the students with the auditory learning style and that of with the kinesthetic learning style; and (4) in the visual and kinesthetic learning styles, the cooperative learning model of the STAD type with SAVI approach and that of the TPS type with SAVI approach result in a better learning achievement than the conventional learning model, and both the cooperative learning model of the STAD type with SAVI approach and that of the TPS type with SAVI approach result in the same learning achievement; in the auditory learning style, the cooperative learning model of the TPS type with SAVI approach results in the same learning achievement as that of the STAD type of SAVI approach and the conventional learning model, but the cooperative learning model of the STAD type with SAVI approach results in a better learning achievement than the conventional learning model. Keywords: STAD, TPS, SAVI, Learning Style, Learning Motivation.